DISKURSUS MANAJEMEN KONFLIK BERBASIS ORGANISASI KEMASYARAKATANPERKOTAAN DI YOGYAKARTA - Ali Maksum; Nur Azizah (Universitas Ahmad Dahlan, 2020)
This article discusses the results of advocacy on conflict management based on urban community organizations, especially the organization 'Aisyiyah, Wirobrajan Branch, Yogyakarta City. This is important considering that the trend of conflict between religious organizations in Yogyakarta City shows serious concerns. This is because in a survey conducted in 2016, the conflict index for the City of Yogyakarta had the highest score, namely 1.4 compared to the other four districts. Thus, this dedication becomes important so that it is expected to reduce the level of conflict within the organization as an effort to self-retraint (restraint) in the Social Constructivism Theory initiated by Alexander Wendt. In this study, the authors conducted a survey which was divided into two periods, namely pre-test before mentoring and post-test after mentoring. As a result, an interesting trend emerged, namely an increase in understanding of governance before and after the material. The ability to internalize conflict management is influenced by several factors, one of which is urban locations that tend to have open discourses and attitudes in society